2010
DOI: 10.3137/oc317.2010
|View full text |Cite
|
Sign up to set email alerts
|

The International polar year (IPY) circumpolar flaw lead (CFL) system study: Overview and the physical system

Abstract: The Circumpolar Flaw Lead (CFL) system study is a Canadian-led International Polar Year (IPY) initiative with over 350 participants from 27 countries. The study is multidisciplinary in nature, integrating physical sciences, biological sciences and Inuvialuit traditional knowledge. The CFL study is designed to investigate the importance of changing climate processes in the flaw lead system of the northern hemisphere on the physical, biogeochemical and biological components of the Arctic marine system. The circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 44 publications
(45 reference statements)
2
76
0
Order By: Relevance
“…Mesoscale eddies in the Beaufort and Chukchi seas are now recognized as an important mechanism for transporting particulate matter from the shelf to the slope and basin environments, thus contributing to both the land-ocean transfer of terrigenous material and to the biological pumping of carbon to depth (Forest et al, 2008;Honjo et al, 2010;O'Brien et al, 2011O'Brien et al, , 2013Watanabe et al, 2014). During winter, the bottom-intensified and slowly-decaying configuration of the shelf-break jet raises the possibility that the Pacific water is mainly routed toward the Canadian Archipelago , thus enhancing the presence of the shelfbreak current and related eddy generation activity to the east -as observed by Barber et al (2010).…”
Section: Introductionmentioning
confidence: 88%
“…Mesoscale eddies in the Beaufort and Chukchi seas are now recognized as an important mechanism for transporting particulate matter from the shelf to the slope and basin environments, thus contributing to both the land-ocean transfer of terrigenous material and to the biological pumping of carbon to depth (Forest et al, 2008;Honjo et al, 2010;O'Brien et al, 2011O'Brien et al, , 2013Watanabe et al, 2014). During winter, the bottom-intensified and slowly-decaying configuration of the shelf-break jet raises the possibility that the Pacific water is mainly routed toward the Canadian Archipelago , thus enhancing the presence of the shelfbreak current and related eddy generation activity to the east -as observed by Barber et al (2010).…”
Section: Introductionmentioning
confidence: 88%
“…Scatterometer and physical data for our study were collected in the southern Beaufort Sea in the winter of 2008 from the research icebreaker CCGS Amundsen as part of the Circumpolar Flow Lead (CFL) system study [29]. Three sites (case studies) representing mobile snow-covered FY sea ice (1.2, 1.2, and 1.1 m thick, respectively) were selected for our analysis (as shown in Table I …”
Section: Experimental Datamentioning
confidence: 99%
“…b ABL Water Vapour Density Profiles As part of the instrumentation aboard the CCGS Amundsen during the IPY-CFL field campaign (Barber et al, 2010), a Radiometrics MP-3000A © microwave radiometer measured atmospheric temperature and water vapour density profiles (50 m intervals from 0 to 500 m, 100 m intervals from 500 to 2000 m, and 250 m intervals from 2000 to 10,000 m) with high temporal (approximately 1 minute) resolution at various locations over Amundsen Gulf. Temperature and water vapour density profiles were derived using the manufacturer's neural network that had been trained using measurements from the nearest operational upper-air station at Inuvik, Canada (68.30°N; 133.47°W).…”
Section: Datamentioning
confidence: 99%
“…In this study, hour-to-hour changes in near-surface (0-500 m) MWR vapour density profiles observed from January through April 2008 of the International Polar Year, Circumpolar Flaw Lead (IPY-CFL) system study (Barber et al, 2010), and the principle of moisture conservation were used to determine latent heat flux convergence/ divergence profiles. The integral profile method (the vertical integration of latent heat flux convergence or divergence) was then used to estimate the mesoscale latent heat flux (Q E ) at the unconsolidated sea-ice surface of Amundsen Gulf in Canada's western maritime Arctic.…”
Section: Introductionmentioning
confidence: 99%